Visible and shortwave near infrared spectroscopy to predict sugarcane quality from clear and raw juice samples - Mat Nawi, Nazmi; Chen, Guangnan; Jensen, Troy (2013)
The feasibility of using visible and shortwave near infrared (Vis/SWNIR) spectroscopy to predict soluble solids content (brix) and sucrose content (pol) from sugarcane juice samples was assessed. A total of 96 sugarcane juice samples for each clear and raw juice samples were used. The spectral measurements were collected by scanning the juice samples in a cuvette with 1 mm path length using transmittance mode. Principal component analysis (PCA) and partial least squares (PLS) analysis were used to interpret the spectra and develop both calibration and prediction models. The prediction performances for the clear juice samples were good with coefficient of determination (R2) values of brix and pol were 0.85 and 0.87, respectively. For the raw juice samples, the prediction performances were acceptable with R2 values for brix and pol were 0.72 and 0.75, respectively. The overall results indicated that the Vis/SWNIR spectroscopy combined with PLS models could be applied to predict sugarcane quality from both clear and raw sugarcane juices.